Method for evaluating hot property of mold

By employing a cylindrical test piece with a specific ratio and heat-resistant sheets, the method accurately measures hot compressive strength and flexibility, addressing the limitations of conventional methods by reducing measurement variations and improving reliability.

JP2024178618APending Publication Date: 2024-12-25ASAHI YUKIZAI KOGYO CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023096890
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2024-12-25

AI Technical Summary

Technical Problem

Conventional hot creep testing methods for molds fail to directly measure hot compressive strength and suffer from large variations and measurement errors due to difficulty in concentrating stress in the center, leading to unreliable results.

Method used

A method using a cylindrical test piece with a specific height-to-diameter ratio (1.2 to 1.8) and heat-resistant sheets at both ends, subjected to hot heat exposure with compressive load measurement via a load cell and displacement monitoring, allowing stress concentration at the center and accurate evaluation of hot properties.

Benefits of technology

This approach enables direct measurement of hot compressive strength and flexibility, reducing measurement variations and improving accuracy by concentrating stress at the center of the test piece, thus enhancing the reliability of the evaluation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178618000001_ABST
    Figure 2024178618000001_ABST
Patent Text Reader

Abstract

To provide: an evaluation method excellent in the hot properties of a mold; an evaluation method capable of directly measuring compressive strength in hot; and a method capable of reducing a measurement variation with respect to a test piece to more accurately evaluate the hot properties.SOLUTION: When the method according to the invention evaluates hot properties of a mold consisting of a molding sand composition by performing heat treatment through exposure to heat on a test piece 10 formed of molding sand composition used for forming a mold, the method forms a configuration where, as the test piece 10, a cylindrical body having of a ratio (h / d) of a height (h) to a diameter (d) falling with in a range between 1.2 and 1.8, and having a continuous outer surface is used, and at both axial ends of the cylindrical body, heat resistant sheets 6 and 8 are arranged, and In the configuration, the method causes upper and lower heat resistant supports to clamp the test piece, and then, causes predetermined heat treatment through exposure to heat to be performed.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for evaluating hot properties of a mold, and more particularly to a technique that can advantageously measure compressive strength at high temperatures and the relationship between fracture time and displacement. [Background technology]

[0002] In the process of producing a desired casting by pouring a specified molten metal into a mold made from a molding sand composition, in order to solve problems such as casting defects that occur, the hot strength and flexibility, such as twistability, of such a mold have been evaluated.

[0003] For example, Japanese Patent Application Laid-Open No. 2009-300347 points out that a hot creep test has been performed using an apparatus having a structure as shown in Fig. 8 of the publication to evaluate hot compressive resistance and formability. That is, a constant compressive load is applied to a test piece by a pressing rod, and the test piece to which the constant load is applied is exposed to a nitrogen gas flow in a movable electric furnace heated to a temperature in the range of 600°C to 1200°C or to the air atmosphere, thereby exposing the test piece to hot heat and performing evaluation. Also, the test piece used there is shown to have a cylindrical shape of a predetermined length (see Fig. 10).

[0004] However, such conventional hot creep testing methods have the problem that the hot strength of the test piece cannot be measured directly, and in addition, when the test piece is exposed to heat, it is difficult to concentrate stress at the center of the test piece. As a result, the measured values ​​vary widely, errors occur in the measurement results, and the test results lack reliability. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2009-300347 A Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been made in light of the above circumstances, and has as its object to provide a method for evaluating the hot properties of a mold with superior properties. Another object of the present invention is to provide an evaluation method capable of directly measuring the compressive strength at high temperatures, and further to provide a method capable of evaluating the hot properties more accurately by reducing the measurement variation for test pieces. [Means for solving the problem]

[0007] In order to solve the above-mentioned problems, the present invention can be preferably implemented in various aspects as listed below, and each aspect described below can be adopted in any combination. It should be understood that the aspects and technical features of the present invention are not limited to those described below, but can be recognized based on the inventive idea disclosed in the description of the entire specification and the drawings.

[0008] In order to solve the above-mentioned problems, the present invention provides a method for evaluating the hot properties of a mold, which comprises using a test piece made of a molding sand composition used for mold making and subjecting it to a hot exposure heat treatment to evaluate the hot properties of a mold made of such a molding sand composition, the test piece being a cylinder having a continuous outer surface and a ratio (h / d) of height (h) to diameter (d) within a range of 1.2 to 1.8, and the cylinder having heat-resistant sheets disposed at both axial ends thereof is sandwiched between upper and lower heat-resistant supports to perform a predetermined hot exposure heat treatment.

[0009] In addition, according to one preferred embodiment of the method for evaluating the hot properties of a mold according to the present invention, the test piece is subjected to a hot heat exposure treatment, while a compressive load is applied in the axial direction of the test piece, and the compressive load is measured by a load cell connected to the upper heat-resistant support of the upper and lower heat-resistant supports, thereby determining the hot compressive strength at which the test piece breaks.

[0010] According to another preferred embodiment of the method for evaluating the hot properties of a mold according to the present invention, a constant load is applied in the axial direction of the test piece by a weight attached to the upper end of the upper heat-resistant support of the upper and lower heat-resistant supports, while the test piece is subjected to a hot heat exposure treatment. At the same time, the time until the test piece breaks and the change in its axial length are measured using a displacement meter that detects the position of the upper heat-resistant support or the weight, which is displaced in the vertical direction during the hot heat exposure treatment.

[0011] Furthermore, according to another preferred aspect of the evaluation method of the present invention, the heat-resistant sheet arranged between the upper end of the test piece and the lower end of the upper heat-resistant support is characterized in that it is composed of a heat-resistant cushion material made of glass wool.

[0012] Furthermore, in the evaluation method according to the present invention, it is preferable that the heat-resistant sheet arranged between the lower end of the test piece and the upper end of the lower heat-resistant support is composed of a heat-resistant woven fabric of ceramic yarn, and that the heat-resistant woven fabric is affixed to the lower end of the test piece.

[0013] In addition, in the present invention, it is preferable that the heat-resistant support is made of a quartz rod. Effect of the Invention

[0014] In this way, according to the method of evaluating the hot properties of a mold according to the present invention, a cylindrical test piece having a continuous outer surface and a height / diameter ratio within a specific range is used, and heat-resistant sheets are placed on both axial ends of the test piece, which is sandwiched between upper and lower heat-resistant supports, and a predetermined hot exposure treatment is performed to evaluate the hot properties.Therefore, during the heat exposure treatment, both ends of the test piece are effectively protected, and stress at high temperatures is effectively concentrated in the central portion of the test piece, thereby effectively suppressing variation in the measurement results and making it possible to easily and accurately evaluate the hot properties of the desired mold.

[0015] Furthermore, by measuring the compressive load applied in the axial direction of the test piece using a load cell connected to the upper heat-resistant support that clamps the test piece, it becomes possible to directly and easily measure the hot compressive strength at which the test piece breaks.

[0016] Furthermore, by using a displacement meter that detects the position of the upper heat-resistant support or weight that clamps the test piece, the change in axial length of the test piece to which a constant load is applied by the weight over the time until the test piece breaks during hot heat exposure treatment, it has become possible to advantageously evaluate hot properties such as the flexibility of the mold. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is an explanatory diagram showing the shape of a test piece used in the present invention, where (a) is an oblique explanatory diagram explaining the height and diameter of a single test piece, and (b) is a front explanatory diagram showing a shape in which heat-resistant sheets are arranged at both axial ends of the test piece. [Diagram 2] FIG. 1 is an explanatory diagram showing an outline of an apparatus for measuring hot compressive strength of a test piece according to the present invention. [Diagram 3] FIG. 1 is an explanatory diagram showing an outline of an apparatus for measuring the hot displacement and rupture time of a test piece according to the present invention. [Figure 4] 3 is a graph showing the relationship between compressive strength and heat exposure treatment time, measured using the device shown in FIG. 2. [Diagram 5] 4 is a graph showing the change in length of a test piece versus heat exposure treatment time, obtained using the device shown in FIG. 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] In order to clarify the configuration of the present invention more specifically, representative embodiments of the present invention will be described in detail below with reference to the drawings.

[0019] First, Fig. 1 shows a schematic diagram of the shape of a test piece (specimen) used in the evaluation method according to the present invention. In the diagram, reference numeral 10 denotes a test piece formed from a molding sand composition used in mold making, and as is clear from the drawing, the test piece 10 is formed to have a solid cylindrical body without notches or slits and therefore a continuous outer surface, in other words, a perfect cylindrical shape.

[0020] In preparing the test piece 10 having such a shape, a conventionally known method can be appropriately adopted, for example, a method of preparing the test piece 10 by filling a molding cavity having a molding cavity corresponding to the shape of the test piece 10 as described above with a molding sand composition used for molding a casting to be evaluated, hardening the molding cavity, and then removing the obtained hardened product from the molding die. The molding sand composition used therein is not limited in type as long as it is used for molding a casting mold, and both sand coated with an organic binder made of a thermosetting resin such as a phenolic resin (RCS) and sand coated with an inorganic binder are applicable.

[0021] In the present invention, as shown in Fig. 1(a), a cylinder having a ratio (h / d) of height (h), which is the length in the axial direction, to diameter (d), which is the size in the direction perpendicular to the axis, within a range of 1.2 to 1.8 is used as the test piece 10. This makes it possible to effectively concentrate the stress (load) applied during the heat exposure treatment (high temperature) at the center portion in the axial direction of the test piece 10, thereby making it possible to reduce the variation in the measured values ​​and advantageously improve the measurement accuracy. If the value of the ratio (h / d) is smaller than 1.2, there is a problem of large variation in the measured values ​​in the measurement of hot compressive strength, as well as in the measurement of the time to break and the maximum displacement. On the other hand, if the value of h / d is larger than 1.8, the test piece 10 as a whole becomes easily crumbled by the heat exposure treatment, making it difficult to measure the compressive strength, and also causing problems such as large variation in the measurements of the time to break and the maximum displacement.

[0022] In the present invention, the ratio of h / d in the test piece 10 is set within the range of 1.2 to 1.8, and a heat-resistant sheet is placed at each end of the axial direction of the test piece 10, and a predetermined hot heat exposure treatment is performed in a state in which the test piece 10 is sandwiched between upper and lower heat-resistant supports, so that the object of the present invention can be better achieved. As the heat-resistant sheet used therein, various known materials having heat resistance capable of withstanding the heat exposure treatment are used, but in particular, in the present invention, as shown in FIG. 1(b), a heat-resistant woven fabric 6 made of ceramic yarn is placed as a heat-resistant sheet at the lower end of the test piece 10 with a thickness of about 0.15 mm to 0.30 mm, and a heat-resistant cushion material 8 made of glass wool is placed as a heat-resistant sheet at the upper end of the test piece 10 with a thickness of about 1.00 mm to 1.80 mm. The heat-resistant woven fabric 6 and the heat-resistant cushioning material 8 are adhered to the lower surface and upper surface of the test piece 10 with an adhesive, respectively, so that they can be held in place.

[0023] By arranging such heat-resistant sheets as the heat-resistant woven fabric 6 or the heat-resistant cushioning material 8 on both axial sides of the test piece 10 and sandwiching them between upper and lower heat-resistant supports as described below, it is possible to prevent both axial ends of the test piece 10 from collapsing first due to the high temperature heat during heat exposure treatment, which would make it difficult to effectively apply stress (load) to the test piece 10, thereby effectively contributing to suppressing variation in the measurement values.

[0024] An example of an apparatus for evaluating hot properties of a mold by performing a predetermined hot exposure treatment using such a test piece 10 is shown in Fig. 2. That is, in Fig. 2, the test piece 10 is subjected to a hot exposure treatment at a temperature of, for example, about 600°C to 1200°C, while a compressive load is applied in the axial direction of the test piece 10 to determine the hot compressive strength at which the test piece 10 breaks.

[0025] 2, 12 is an upper base that is held in a fixed position, 14 is a lower base that is movable in the vertical direction, and 16 is a cylindrical electric furnace that is movable in the vertical direction. A cylindrical lower quartz rod 18 of a given length, which is a heat-resistant support, is erected on the lower base 14, while a load cell 20 for measuring compressive strength is attached to the lower side of the upper base 12, and a cylindrical upper quartz rod 24 of a given length, which is a heat-resistant support, is attached in a hanging manner to the lower side of the load cell 20 via a movable attachment base 22.

[0026] In this device configuration, the test piece 10 having the configuration shown in Fig. 1(b) is placed on the upper surface of the lower quartz rod 18 via the heat-resistant woven fabric 6, and then the lower base 14 is moved upward, so that the upper end of the test piece 10 is brought into contact with the lower surface of the upper quartz rod 24 via the heat-resistant cushion material 8, and the test piece 10 is sandwiched between the lower quartz rod 18 and the upper quartz rod 24. Furthermore, in this state, the electric furnace 16 is moved upward, and the test piece 10 is positioned in the electric furnace 16 to perform heat exposure treatment, while the lower base 14 is moved upward to apply a compressive load to the test piece 10, and the pressure at that time is measured by the load cell 20 via the upper quartz rod 24 and the mounting base 22, and the target hot compressive strength is obtained.

[0027] 3 shows an apparatus configuration for subjecting the test piece 10 to a hot heat treatment while applying a constant load to the test piece 10 in its axial direction, and measuring the time until the test piece 10 breaks and its change in length in the axial direction. A weight 26 for applying a predetermined constant load (e.g., 2.5 kg) to the test piece 10 via an upper quartz rod 24 is placed on a movable mounting base 22, and a digimatic indicator 28, which is a displacement meter for detecting the vertical position (displacement) of the weight 26, is fixedly disposed in a state in which its probe is in contact with the weight 26, so that the axial length of the test piece 10, which changes with the passage of the hot heat treatment time, can be measured under a constant load.

[0028] That is, in the apparatus configuration shown in FIG. 3, when measuring the hot displacement and fracture time of the test piece 10, the lower base 14 is moved upward, and the test piece 10 placed on the lower quartz rod 18 is brought into close contact with the lower end surface of the upper quartz rod 24, and is sandwiched between the lower quartz rod 18 and the upper quartz rod 24 via the heat-resistant woven fabric 6 and the heat-resistant cushion material 8. In this configuration, the electric furnace 16 is raised, and the test piece 10 is subjected to a heat exposure treatment (for example, at a temperature of 600°C to 1200°C) under the load of a constant load by the weight 26. The axial hot displacement of the test piece 10 based on this, in other words, the negative change in the axial length, is measured by the digimatic indicator 28 until the test piece 10 fractures, and the relationship between the hot displacement and the fracture time is obtained.

[0029] The results of measurements using the apparatuses configured as shown in Fig. 2 and Fig. 3 are shown in Fig. 4 and Fig. 5, respectively. That is, Fig. 4 shows the relationship between the elapsed time (seconds) of the heat exposure treatment and the compressive strength, and the peak value of the compressive strength is recognized as the hot compressive strength when the test piece 10 breaks. In the measurement of the hot compressive strength, the test piece 10 is held in a clamped state for 25 seconds, and then the lower base 14 is further raised, so that a compressive load is applied to the test piece 10. Fig. 5 also shows the relationship between the elapsed time (seconds) of the heat exposure treatment and the negative change in the axial length of the test piece 10, i.e., the negative displacement (mm), and the negative displacement of the test piece 10 gradually increases as the heat exposure time passes, and the maximum point of the negative displacement can be recognized as the break point of the test piece 10.

[0030] In this way, by measuring the hot compressive strength of the test piece 10 and the amount of hot displacement with respect to the heat exposure treatment time and evaluating the hot characteristics of the mold, it is possible to directly measure the hot compressive strength. In addition, even if both ends of the test piece 10 are exposed to high heat, the both ends of the test piece 10 can be abutted / closely attached to the upper and lower quartz rods 24, 18 by interposing heat-resistant sheets (8, 6) between them. In addition, the test piece 10 is configured to have a size such that the ratio of height to diameter (h / d) is 1.2 to 1.8. This makes it possible to effectively concentrate stress at high temperatures in the axial center of the test piece 10. This makes it possible to advantageously reduce the variation in measurements for each test piece 10 and effectively improve the measurement accuracy.

[0031] Although the embodiment of the present invention has been described in detail above, it should be understood that this is merely an example and that the present invention is not limited in any way by the above description.

[0032] For example, in the device configuration shown in FIG. 3, in order to measure the change in axial length of the test piece 10 due to heat exposure treatment, the vertical change of the weight 26 can be detected by contacting the probe of the digital indicator 28 with the weight 26 via the upper quartz rod 24 and the mounting base 22, and the amount of displacement can be detected. However, it is also possible to directly measure the vertical displacement of the upper quartz rod 24 with a specified displacement meter, or to indirectly measure the displacement of the upper quartz rod 24 by measuring the displacement of the mounting base 22, which displaces in the vertical direction together with the upper quartz rod 24.

[0033] In addition, although not listed one by one, the present invention can be implemented in various forms with various changes, modifications, improvements, etc. based on the knowledge of those skilled in the art, and it goes without saying that all such embodiments fall within the scope of the present invention as long as they do not deviate from the spirit of the present invention. EXAMPLES

[0034] Hereinafter, some examples of the present invention will be shown to clarify the features of the present invention more specifically, but it should be understood that the present invention is not limited in any way by the description of such examples. In the following examples, "parts" and "percentages" are all expressed on a mass basis.

[0035] -Production of novolac phenolic resin- Into a reaction vessel equipped with a thermometer, a stirrer, and a condenser, 940 parts of phenol, 428 parts of 47% formalin, and 2.8 parts of oxalic acid were respectively charged. Next, the temperature of the reaction vessel was gradually raised until it reached the reflux temperature, and then the mixture was refluxed for 90 minutes to react, and further concentrated under reduced pressure while heating until the reaction liquid temperature reached 170°C, thereby obtaining 850 parts of a novolac type phenolic resin.

[0036] -Production of molding sand composition- (1) Manufacturing of RCS1 140 parts of the above novolac-type phenolic resin was added to 7,000 parts of regenerated silica sand (SiO2 content: 88%) heated to 150°C, and mixed for 50 seconds in a speed mixer. Then, a solution of 21 parts of hexamethylenetetramine dissolved in 105 parts of water was added and mixed until the sand separated into individual particles. 7 parts of calcium stearate was further added and mixed for 15 seconds, and the mixture was removed from the mixer to obtain RCS1, a resin-coated sand that is a molding sand composition. (2) Manufacturing of RCS2 140 parts of the novolac phenolic resin was added to 3,500 parts of new sand (natural silica sand from Australia, product name: Flattery Sand) heated to 150°C and 3,500 parts of regenerated silica sand (SiO2 content: 88%), and mixed for 50 seconds in a speed mixer. Then, a solution of 21 parts of hexamethylenetetramine dissolved in 105 parts of water was added and mixed until the sand separated into individual particles. 7 parts of calcium stearate were further added and mixed for 15 seconds, and the mixture was removed from the mixer to obtain the foundry sand composition RCS2. (3) Manufacturing of RCS3 140 parts of the above novolak-type phenolic resin was added to 7,000 parts of new sand (natural silica sand from Australia, product name: Flattery Sand) heated to 150°C, and the mixture was kneaded for 50 seconds in a speed mixer. Then, a solution of 21 parts of hexamethylenetetramine dissolved in 105 parts of water was added and the mixture was kneaded until the sand separated into individual particles. Further, 7 parts of calcium stearate were added and mixed for 15 seconds, and the mixture was removed from the mixer to obtain the desired resin-coated sand, RCS3.

[0037] -Preparation of test piece (10)- A mold capable of being split into halves was prepared, in which six molding cavities each having a diameter x height size of 16 mm x 20 mm, 12 mm x 20 mm, 10 mm x 20 mm, or 20 mm x 20 mm were formed in series on the parting surface. Next, using this mold, the RCS1, RCS2, or RCS3 obtained above was filled into each mold while being vibrated at room temperature, and each RCS that overflowed and raised on the mold surface was scraped off with a spatula, and then the mold was left to stand for 6 minutes in an electric furnace previously heated to 260 ° C. After the 6 minutes had elapsed, the mold was taken out of the electric furnace and opened to remove the formed test piece (10), which was then cooled to room temperature and subjected to the following tests. Note that 12 test pieces (10) for each RCS were prepared, numbered TP1 to TP12, and used for each measurement.

[0038] -Measurement of hot compressive strength- Using 12 pieces of each of the various test pieces (10) produced as described above, the hot compressive strength (MPa) after heat exposure treatment at 1000°C for 25 seconds in an air atmosphere was determined in the apparatus configuration shown in FIG. 2, and the measurement variation in the hot compressive strength of the 12 test pieces (10) was evaluated.

[0039] -Measurement of maximum displacement and time to break- For each of the 12 test pieces (10) produced using each of the RCSs, a constant load heat treatment of 1000°C x 2.5 kgf (mass of the weight 26) was performed in an air atmosphere using the apparatus configuration shown in Figure 3, and the variations in the measured values ​​of the maximum displacement (mm) and the breakage time (seconds) for each of the 12 test pieces (10) were evaluated.

[0040] -Measurement results- The evaluation results of the hot compressive strength are shown in Table 1 below, and the measurement results of the maximum displacement and the time to break are shown in Tables 2 and 3 below, respectively.

[0041] [Table 1]

[0042] [Table 2]

[0043] [Table 3]

[0044] - Review of measurement results - As is clear from the comparison of the measured values ​​of hot compressive strength after heat exposure treatment at 1000°C for 25 seconds for 12 test pieces (10) shown in Table 1 above, by arranging heat-resistant sheets (6, 8) at both axial ends of the test piece (10) according to the present invention and using a test piece (10) having an h / d ratio within the range of the present invention, it is possible to obtain measured values ​​with small variation in hot compressive strength values, i.e., small standard deviation, as shown in Experimental Examples 1 to 4.

[0045] In contrast, in Comparative Example 1, in which the heat-resistant sheets 6, 8 are not provided at both ends of the test piece 10, and Comparative Example 3, in which the h / d ratio is below the range specified in the present invention, the standard deviation is large, and therefore the measured values ​​vary widely. In Comparative Example 2, the results are shown for a test piece 10 with an h / d ratio greater than the range specified in the present invention, but the test piece 10 is brittle and may collapse due to heat exposure, making it impossible to measure the hot compressive strength, and the measured value is extremely low, making it difficult to obtain a normal hot compressive strength value.

[0046] Furthermore, as is clear from Tables 2 and 3 showing the results of the maximum displacement and the time to break measured simultaneously in the apparatus configuration shown in FIG. 3, in Experimental Examples 5, 6, 7, and 8 in which heat-resistant sheets (6, 8) were placed on both axial ends of the test piece (10) according to the present invention and the h / d ratio of the test piece (10) was within the range of the present invention, the standard deviations of the maximum displacement (mm) and the time to break (seconds) for the 12 test pieces (10) were small, and therefore it can be seen that measurement values ​​with little variation were obtained.

[0047] In contrast, in the measurement results of the maximum displacement (mm) and the time to break (sec) for the 12 test pieces (10) shown in Comparative Examples 4, 5 and 6, the standard deviation is significantly large, and therefore the variation in the measurement values ​​is large, making it difficult to obtain accurate measurement values. [Explanation of symbols]

[0048] 6. Heat-resistant woven fabric 8. Heat-resistant cushioning material 10 Test Pieces 12 Upper pedestal 14 Lower pedestal 16 Electric furnace 18 Lower quartz rod 20 Load Cells 22 Mounting base 24 Upper quartz rod 26 weight 28 Digimatic Indicator

Claims

1. In order to evaluate the hot properties of a mold made of a molding sand composition by subjecting a test piece formed of the molding sand composition to a hot exposure heat treatment, The method for evaluating hot characteristics of a mold is characterized in that the test piece is a cylinder having a continuous outer surface and a ratio (h / d) of height (h) to diameter (d) within a range of 1.2 to 1.8, and the cylinder is sandwiched between upper and lower heat-resistant supports in a form in which heat-resistant sheets are placed on both axial ends of the cylinder, and a predetermined hot exposure treatment is performed.

2. The method for evaluating the hot properties of a mold according to claim 1, characterized in that while the test piece is subjected to a hot heat exposure treatment, a compressive load is applied to the test piece in the axial direction, and the compressive load is measured by a load cell connected to the upper heat-resistant support of the upper and lower heat-resistant supports, thereby determining the hot compressive strength at which the test piece breaks.

3. The method for evaluating the hot properties of a mold as described in claim 1, characterized in that the test piece is subjected to a hot heat exposure treatment while a constant load is applied in the axial direction to the test piece by a weight attached to the upper end of the upper heat-resistant support of the upper and lower heat-resistant supports, and the time until the test piece breaks and the change in its axial length are measured using a displacement meter that detects the position of the upper heat-resistant support or the weight, which is displaced in the vertical direction during the hot heat exposure treatment.

4. 2. A method for evaluating hot properties of a mold as described in claim 1, characterized in that the heat-resistant sheet placed between the upper end of the test piece and the lower end of the upper heat-resistant support is made of a heat-resistant cushion material made of glass wool.

5. A method for evaluating the hot properties of a mold as described in claim 1, characterized in that the heat-resistant sheet placed between the lower end of the test piece and the upper end of the lower heat-resistant support is made of a heat-resistant woven fabric of ceramic yarn, and the heat-resistant woven fabric is affixed to the lower end of the test piece.

6. 6. The method for evaluating hot properties of a mold according to claim 1, wherein the heat-resistant support is made of a quartz rod.

Citation Information

Patent Citations

  • Method and test piece for evaluating mold characteristics

    JP2009300347A